2020
DOI: 10.1002/rra.3589
|View full text |Cite
|
Sign up to set email alerts
|

Associations between riparian plant morphological guilds and fluvial sediment dynamics along the regulated Colorado River in Grand Canyon

Abstract: Effects of riparian vegetation on fluvial sediment dynamics depend on morphological traits of the constituent species. Determining the effects of different morphological guilds on sedimentation rates, as influenced by multiple aspects of dam operations, can help identify viable strategies for streamflow and vegetation management to achieve riparian resource goals. Plants of increasing size and branching density or complexity have been found to have greater effects on sedimentation in free‐flowing systems; howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 60 publications
(104 reference statements)
4
39
0
Order By: Relevance
“…Guild location impacts the morphological response, with analysis of bars showing different responses downstream and also laterally based on the traits of the dominant species in these directions (Hortobágyi et al, 2018). This is supported by Butterfield et al (2020) who when examining changes in multi-annual elevation found that guilds at different locations, experiencing different hydraulic conditions, had differing impacts, but also that guilds could not explain all the variation in morphological response. It was found that differing canopy https://doi.org/10.5194/esurf-2021-102 Preprint.…”
Section: The Importance Of Vegetationmentioning
confidence: 85%
See 2 more Smart Citations
“…Guild location impacts the morphological response, with analysis of bars showing different responses downstream and also laterally based on the traits of the dominant species in these directions (Hortobágyi et al, 2018). This is supported by Butterfield et al (2020) who when examining changes in multi-annual elevation found that guilds at different locations, experiencing different hydraulic conditions, had differing impacts, but also that guilds could not explain all the variation in morphological response. It was found that differing canopy https://doi.org/10.5194/esurf-2021-102 Preprint.…”
Section: The Importance Of Vegetationmentioning
confidence: 85%
“…For fluvial research, multispectral imagery can be used to determine species using supervised and unsupervised classifications with good accuracy (Butterfield et al, 2020). Outside of fluvial research there is an increasing awareness of the potential of remote sensing methods to help drive the scalability of functional traits, especially in relation to physical traits such as plant height, leaf area index, phenology, and biomass (Abelleira Martínez et al, 2016;Aguirre-Gutiérrez et al, 2021), yet considerable limitations remain due to the uncertainty in relating spectral and physical properties to functional traits (Houborg et al, 2015).…”
Section: Remote Sensing Of River Corridor Vegetationmentioning
confidence: 99%
See 1 more Smart Citation
“…Expansion and other responses of riparian vegetation to changes in river flow associated with river regulation can differ by species, growth form, plant physiologyand native (invasive) status and can be affected by feedbacks with river sediment (Butterfield et al, 2020;Dean & Topping, 2019;Diehl, Merritt, et al, 2017;Manners et al, 2014). Moreover, river channels and riparian areas comprise a range of geomorphic landforms such as sandbars, gravel bars, talus slopes and tributary debris fans.…”
Section: Introductionmentioning
confidence: 99%
“…While bedrock and coarse sediment such as boulders form the rigid channel boundary, fine sediments comprise a dynamic and transient part of the river corridor (e.g., Skalak & Pizzuto, 2010). Fine sediments provide substrate for riparian vegetation, morphological complexity for the aquatic ecosystem, protection of archeological resources, and important recreational areas for visitors (Butterfield et al., 2020; East et al., 2017; Grams et al., 2010; Kaplinski et al., 2005; Korman et al., 2004; Meshkova & Carling, 2012). In canyon rivers where flow is strongly affected by bedrock or relatively immobile talus, flow hydraulics are often dictated by these fixed obstructions (Alvarez et al., 2016; Rennie et al., 2018; Venditti et al., 2014; Wright & Kaplinski, 2011).…”
Section: Introductionmentioning
confidence: 99%